STUDI PENURUNAN KEKERUHAN DAN TOTAL SUSPENDED SOLIDS (TSS) DALAM BAK PENAMPUNG AIR HUJAN (PAH) MENGGUNAKAN REAKTOR GRAVITY ROUGHING FILTER (GRF) - Samudro, Ganjar; Rulian E, Raden Abadi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2011)
This research investigated the influence of flowrate and turbidity and total suspended solids level to detention time in GRF reactor. The difference of flowrate could produce the difference of turbidity and total suspended solids level at certainly detention time. The research objects were rain water in rain water reservoir and GRF on laboratory bench scale. The research concluded that optimum flowrate is 5 mL/s with 78% reduction efficiency of turbidity and 79%Â  reduction efficiency of total suspended solids level which was 100 minutes operating.